PEMBANGUNAN MANUSIA VERSUS PERTUMBUHAN EKONOMI: ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN IPM TERHADAP KEMISKINAN DI KABUPATEN GOWA TAHUN 2016–2024 - Makmuralto, Makmuralto; L. Manduapessy, Rulan (STIE Jambatan Bulan, 2026)
This study examines the relationship between human development, economic growth, and poverty levels in Gowa Regency during the period 2016–2024, using official statistical data from the Central Bureau of Statistics (BPS). A quantitative research design was applied, incorporating descriptive statistical analysis, Pearson correlation testing, and multiple linear regression to assess the role of economic growth and the Human Development Index (HDI) in explaining poverty variable. The results show that economic growth has a moderate but statistically insignificant positive correlation with poverty, suggesting that higher economic output did not directly contribute to poverty reduction. Conversely, HDI demonstrates a strong and statistically significant negative association with poverty, indicating that progress in education, health, and living standards had a more substantial effect on reducing poverty levels. Regression findings confirm that HDI is the only significant determinant, explaining most of the model’s variation. These findings highlight that human development plays a more decisive role in poverty reduction than economic growth alone in Gowa Regency